Why timing is everything: Energetic costs and reproductive consequences of resource mismatch for a chick‐rearing seabird. Issue 12 (22nd December 2014) - Regular, Paul M.; Hedd, April; Montevecchi, William A.; Robertson, Gregory J.; Storey, Anne E.; Walsh, Carolyn J.
Abstract : Timing reproduction to overlap with peak prey availability is vital to success for many species. This may be especially true for species that rely on one or a few prey species that exhibit strong seasonal peaks in abundance. Any mismatch must be mediated by parents that provision offspring through flexible behavioral changes within the bounds of their physiological tolerances. In Newfoundland, common murre Uria aalge breeding coincides with the inshore movement of capelin Mallotus villosus —their primary prey—such that peak prey availability overlaps with chick‐rearing, the most energy demanding phase of breeding. We use colony‐based observations and temperature‐depth recorders to track the behavioral responses of murres to temporal match and mismatch with capelin availability. Activity budgets, daily energy expenditure (DEE) and chick‐provisioning rates were constant across years when chick and capelin timing matched. However, when capelin were late, despite increasing diving effort and DEE, parents delivered fewer fish to chicks per day and reduced breeding success was observed. While parents partially buffered the effects of variable capelin abundance by reducing co‐attendance time (time spent at the colony with mates) and increasing foraging time, physiological constraints on energy output likely limited their ability to maintain chick‐provisioning rates in a mismatch year. Such responses could have demographic consequences if ocean climate changes decouple the timing of chick‐rearing and prey availability.